Introducing “Disrupted Histories, Recovered Pasts” - Sian Sullivan; Michèle Baussant; Lindsey Dodd; Olivette Otele; Irène Dos Santos (Conserveries Mémorielles)
This introductory paper outlines the conceptual framework and case studies comprising the research project Disrupted Histories, Recovered Pasts. Our project proposes a cross-disciplinary analysis and cross-case synthesis of experience and memory in post-conflict and postcolonial contexts. In the post- conflict and colonial contexts of our cases, we see “disruption” as present in three senses: as the productive ways in which multiple experiences retrieved through oral histories may refract and revise historical analysis; as the happening histories of objectively disruptive events break the flow of individual and collective experience; and as a strategy for cross-disciplinary research to disrupt and democratise conventional understanding by drawing attention to occluded experiences. We also articulate “recovery” as polysemic: invoking retrieval of past experiences and the possibility for enhanced well-being through voicing memories that may have been suppressed, as well as attending to mismatches with public discourses about displaced groups and individual experience. Following an introduction to our conceptual approach, we summarise our case-research. We have conducted oral history and archival research in multiple contexts, from disciplinary bases in anthropology and history. Our aim has been to interrogate relationships between oral histories and amateur histories with more formal written archives and historiography in a series of disrupted settings: evictions in colonial and apartheid west Namibia (SULLIVAN); memories and historical interpretations of the Egyptian Jewish diaspora (BAUSSANT); the evacuation of children in Second World War France (DODD); recent maritime exodus of migrants from Africa (OTELE); and rupture from a hegemonic imperial-nostalgic narrative in Portugal (DOS SANTOS). Our case research is complemented in the concluding paper of this Special Issue by systematic cross-case engagement, synthesis and theorisation of our case-study research.